Sound Recordings Relating to the Conflict in the former Yugoslavia
Approximately 23 hours of live coverage of the activities of fact-finding missions in the Former Yugoslavia intended to reveal crimes committed during the war. They include sound recordings made during exhumations and forensic examinations; testimonies of victims of ethnic cleansing in Kozarac (Bosnia); Četekovac, Ilok, Kusonje, Pakrac and Vukovar (Croatia). Rough, unedited recordings of the shelling of Dubrovnic (Croatia), with civilians' comments on the attack are also part of the series. Radio programs about Muslim women raped during the war in the Former Yugoslavia are also included. Accruals not expected